One-step electrodeposition of cerium-doped nickel hydroxide nanosheets for effective oxygen generation. Issue 31 (6th June 2019) - Fang, Gang; Cai, Jinhua; Huang, Zhipeng; Zhang, Chi
Abstract : Cerium doping is effective approach to promoting performance of nickel hydroxide in oxygen evolution reaction. Abstract : Efficient electrocatalysts catalyzing oxygen evolution reaction (OER) in alkaline media is highly desirable for large-scale hydrogen production from water splitting. Here we report the direct electrodeposition of cerium-doped nickel hydroxide nanosheets on carbon fiber paper and its prominent performance in catalyzing the OER. The composite generates a current density of 100 mA cm −2 at an overpotential of 320 mV, rivaling the performance of most reported OER catalysts and commercially available RuO2 . X-ray photoelectron spectroscopy analysis shows strong electronic interaction between Ni(OH)2 and CeO2, making a great contribution to the OER enhancement.